Peculiarities of cellular composition and microarchitecture of human hemal nodes. - Pototskaya, O. Yu.; Lapsar, A. S. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Cellular composition of lymph nodes is well described while in hemal nodes it is still poorly investigated. Objective. To define peculiarities of distribution of major types of immunocompetent cells and stromal elements in human hemal nodes. Methods. Hemal nodes were taken during autopsy from patients who died due to cardiovascular or respiratory pathology. Standard histological and immunohistochemical methods were used to detect different cellular types and stromal elements. Results. Distributions of lymphocytes was investigated with the help of anti-CD20, CD3 and CD8 antibodies. To analyze dendritic cells and macrophages anti S100 and CD68 antibodies were used. Stromal elements were detected with the help of anti SMA and CD34 antibodies. Conclusion. Hemal nodes have the same character of immune cells’ distribution as in lymph nodes, except B-cells, which are equally present in paracortex and medullary cords. Among well-developed intranodal vasculature there were revealed CD34-negatve vessels, which are also known in literature as system of conduits.